Taxonomic and functional diversity of aquatic heterotrophs is sustained by dissolved organic matter chemodiversity - Garcia, Sarahi (Stockholm University, 2022)
With this study, we advance the understanding of how specific aquatic heterotrophic bacteria act as central agents in the microbial loop. We use cultivated model communities developed from lake bacterioplankton under selection (i) in coculture with the cyanobacterium Microcystis aeruginosa (ii) growing on DOM produced from an axenic culture of M. aeruginosa, and (iii) growing in ambient lake DOM. After dilutions and serial transfer, cultivated model communities were established and characterized with a powerful combination of genome-resolved metagenomics and high-resolution untargeted metabolite analysis. This repository contains all metagenome-assembled genomes (MAGs) used in the study. The study is currently in bioRxiv https://www.biorxiv.org/content/10.1101/2022.03.21.485019v1

Each entry in the database corresponds to a MAG assembled from a cultured model community from Lake Erken. We had 33 cultures, 5 originated from inoculation on spent media from axenic M. aeruginosa (DOM$$_bin-**.fasta, where $$ is the numnber of the culture and ** is the MAG number), 21 cultures originated from filtered sterilized lake water (ERK$$_bin-**.fasta, where $$ is the numnber of the culture and ** is the MAG number) and 7 cultures were established as co-cultures with M. aeruginosa (CO$$_bin-**.fasta, where $$ is the numnber of the culture and ** is the MAG number) or to a MAG assembled from Lake Erken (Erken$$_bin-**.fasta, where $$ is name of the sample and ** is the MAG number).
Keywords: Freshwater ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi